Vacuum vaporizer for fabrication of thin films of material by sublimations - A. I. Blesman; R. B. Burlakov (Омский научный вестник)
The offered vacuum vaporizer can be used under the vacuum fabrication of films from Cr, Mg, Mn, SiO, GeO, MoO3 , WO3, ZnS, ZnSe, CdS, CdSe, CdTe by sublimations. Vacuum vaporizer containing tubular element with tightly closed by flat end areas, executed from Та (or Мо) foil by the thickness (0,05–0,1) mm with the high temperature of melting and evaporations and is kept a central region of the radial cross-section with the hole in the manner of the oval situated between flat end areas having variable area of the current section, which decreases toward from the centre of the tubular element to its ends. The offered vaporizer has broader field-performance and technological possibilities, since for the fabrication of the vaporizer use a metallic foil that allows under its fabrication to change amounts of the vaporizer. Herewith the vaporizer possible to use for fabrication of films repeatedly executing its recurrent boot without removing from the vacuum camera.